Synthesis, characterization and simulation of lithium titanate nanotubes for dye sensitized solar cells. Issue 1 (January 2019) - Esteves, Martín; Fernández-Werner, Luciana; Pignanelli, Fernando; Montenegro, Benjamín; Belluzzi, Marcelo; Pistón, Mariela; Chialanza, Mauricio Rodríguez; Faccio, Ricardo; Mombrú, Álvaro W.
Abstract: In this work we present the comprehensive design of lithium titanate nanotubes (LiTNT) as semiconductors for DSSC photoanodes. The synthesis and characterization of Li1.82 Na0.18 Ti3 O7 .nH2 O nanotubes was performed and a prototype of cell using this material was assembled. The cell exhibited a 7.7% efficiency and a relatively high open circuit voltage, Voc = 0.72 V. In comparison with previously obtained hydrogen titanate nanotubes (HTNT), improvements have been achieved, like better charge carriers' lifetime and lower series resistance. In order to study this system, we carried out previous DFT simulations for this lithium titanate nanotubes through different model's complexity levels which were able to correctly predict its properties. Due to the improvements achieved this system would encourage further studies with the aim to explore its potential for solar cells applications.